Efektivitas Tepung Daun Mangrove untuk Mengendalikan Penyakit Vibriosis pada Larva Udang Vaname (Litopenaeus vannamei) - Arifah, Sitti; Amrullah; Wahidah; Ardiansyah; Khatimah, Khusnul (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2024)
Shrimp production in several Asian countries, including Indonesia, accounts for more than 85% of world production, thus control of shrimp larval diseases must be strengthened to increase production. This study aimed to test the effectiveness of mangrove leaves, Rhizopora sp, in controlling larval vibriosis of the vannamei shrimp (Litopenaeus vannamei). The study began with in vitro tests to evaluate the antimicrobial activity of mangrove leaf flour against Vibrio sp bacteria at doses of 400, 500, 600, 700, 800, 900, 1000 mg/L, 5% amoxicillin antibiotic (K+) and without mangrove flour (K). In the in vivo test, vannamei shrimp larvae (mysis-3) were immersed in a solution containing mangrove leaf flour with the three best doses of in vitro test results; 800, 900, and 1000 mg/L water, plus K-, for 15 minutes according to the treatment dose and maintained for 8 days before being challenged with Vibrio spp. The parameters observed were total hemocyte count (THC), differential hemocyte count (DHC), and survival rate (SR), which were observed on days 1 and 8, respectively, with the SR parameter observed on day 7 following the challenge test. The results showed that the Mangrove leaf diet at 800 and 900 mg/L significantly improved larval resistance to the pathogen V. harveyi (P < 0.05). The high resistance was triggered by THC immunological response and the high proportion of semi-granular and hyaline at doses of 800 and 900 mg/L (P<0.05). Mangrove leaf powder can therefore suppress vibriosis disease in vanamei shrimp larvae using the immersion method at 800 and 900 mg/L concentrations.